2020
DOI: 10.1109/access.2020.3017372
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the Features of NOCT and NMOT Tests With Photovoltaic Module

Abstract: The operating temperature of the photovoltaic (PV) module plays a major role among the parameters affecting the energy yield of photovoltaic (PV) power generation systems. This paper compared the requirements of Nominal Operating Cell Temperature (NOCT), which is used to estimate the PV module operating temperature according to IEC 61215:2005, with those of the recently revised IEC 61215: 2016 Nominal Module Operating Temperature (NMOT). Through this, each feature of the parameters used to calculate the NOCT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…For a wind speed of 5 m/s with a length of 0.5 m and ambient temperature 25 • C, the suggested model yields 23 W/m K in contrast to available convective heat transfer coefficient of Equations ( 6) and ( 7) that where led to 24 W/m K and 18 W/m K, respectively. Calculating the NOCT temperature according to Equations ( 2) and ( 12) with an assumption of L = 1 m display T C,NOCT = 28.53 + 20 = 48.53 • C which remarkably matches the experimental report for NOCT Tempearure with 45 ± 5 [19,36].…”
Section: Noct Condition and Convection Model Of Wind Speedsupporting
confidence: 76%
“…For a wind speed of 5 m/s with a length of 0.5 m and ambient temperature 25 • C, the suggested model yields 23 W/m K in contrast to available convective heat transfer coefficient of Equations ( 6) and ( 7) that where led to 24 W/m K and 18 W/m K, respectively. Calculating the NOCT temperature according to Equations ( 2) and ( 12) with an assumption of L = 1 m display T C,NOCT = 28.53 + 20 = 48.53 • C which remarkably matches the experimental report for NOCT Tempearure with 45 ± 5 [19,36].…”
Section: Noct Condition and Convection Model Of Wind Speedsupporting
confidence: 76%
“…Although the detailed study of the photovoltaic (PV) module temperature should include heat-transfer phenomena analysis [16,17], which would lead to transient temperature models, the alternative, analytical steady-state temperature models have been extensively used to determine the PV module temperature in PV plants. These straightforward models only need simple meteorological variables as an input, and led to acceptable degree of accuracy in the prediction of electrical PV performance in PV plants [18]. Some of the proposed models were found to determine the module temperature with an accuracy comparable to the cell-to-cell temperature differences typically encountered within a module [15,19].…”
Section: Background and Objectivementioning
confidence: 98%
“…Different works have assessed NOCT and NMOT models, generally considering openrack-mounted modules [18,32], but some of them addressing related BIPV configurations also. For instance, Davis et al [33] concluded that the NOCT model underpredicted the module temperatures and found temperature differences of up to 20 degrees between insulated and non-insulated vertically mounted modules.…”
Section: Background and Objectivementioning
confidence: 99%
“…The PV produces heat when electricity is produced. This is based on the normal operating cell temperature (NOCT) test conducted at 800 W/m 2 and 20°C ambient temperature [6]. The PV temperature on average is around 45°C, which is 25°C different from the surrounding.…”
Section: Introductionmentioning
confidence: 99%